2015
DOI: 10.1021/ml500340z
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin Antagonist Tetrapeptides with Minimal Agonist Activity at the Mouse Melanocortin-3 Receptor

Abstract: The melanocortin system regulates many important functions in the body. There are five melanocortin G protein-coupled receptor subtypes known to date. Herein, we report a structure-activity relationship (SAR) study of a tetrapeptide lead discovered through a double substitution strategy at the melanocortin core His-Phe-Arg-Trp sequence. Several compounds were identified with micromolar agonist activity at the mouse melanocortin-1 (mMC1R) and mouse melanocortin-5 receptor (mMC5R) subtypes, weak antagonist activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…From these search parameters, three studies reported selective pA 2 values at two melanocortin receptors (mMC3R and mMC4R) and reported functional agonist EC 50 values for the other two receptors (mMC1R and mMC5R, Table 3) [132-134]. For the sake of clarity, antagonists in Table 3 were divided into two sections: ligands with antagonist activity at the mMC4R but no agonist or antagonist activity observed at the mMC3R at concentrations up to 10 μM (pA 2 < 5) and antagonists that were active at the mMC3R and mMC4R.…”
Section: Selective Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these search parameters, three studies reported selective pA 2 values at two melanocortin receptors (mMC3R and mMC4R) and reported functional agonist EC 50 values for the other two receptors (mMC1R and mMC5R, Table 3) [132-134]. For the sake of clarity, antagonists in Table 3 were divided into two sections: ligands with antagonist activity at the mMC4R but no agonist or antagonist activity observed at the mMC3R at concentrations up to 10 μM (pA 2 < 5) and antagonists that were active at the mMC3R and mMC4R.…”
Section: Selective Compoundsmentioning
confidence: 99%
“…The antagonists reported by Doering et al . were derivatives of the tetrapeptide Ac-Trp-DPhe( p -I)-Arg-Trp-NH 2 [132]. Scaffolds reported by Ericson et al .…”
Section: Selective Compoundsmentioning
confidence: 99%
“…SKY 2-23-7 was characterized as a weak antagonist (pA2=5.43±0.16) at the mMC3R and a strong antagonist (pA2=7.83±0.16) at the mMC4R (Figure 2). Distinctly there was minimal mMC3R agonist activity up to 100 µM which is not commonly observed for a mMC3R/mMC4R antagonist such as SHU9119 [11]. The current study investigated the in vivo effects of this unique pharmacology via intracerebroventricular (ICV) administration of SKY 2-23-7 in male and female mice which gave evidence of sex specific differences.…”
Section: Introductionmentioning
confidence: 94%
“…SKY 2-23-7 is a tetrapeptide which was identified in our laboratory with the sequence Ac-Trp-(p-I)DPhe-Arg-Trp-NH2 ( Figure 1) [11]. It was discovered through a double substitution strategy of the melanocortin core His-Phe-Arg-Trp sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation